2023
DOI: 10.1590/0103-8478cr20210805
|View full text |Cite
|
Sign up to set email alerts
|

Brown propolis bioactive compounds as a natural antimicrobial in alginate films applied to Piper nigrum L.

Abstract: An edible coating of sodium alginate incorporated with brown propolis (2.5%, 5%, 10%, and 15%) was applied to black pepper grains to improve microbiological quality over 30 days. Gas chromatography coupled with mass spectrometry identified 29 metabolites in the extract, mainly terpene compounds (51.74%), phenolic compounds (25.83%), and flavonoids (14.48%). Brown propolis showed greater antibacterial activity for Gram-positive bacteria (MIC from 0.1 to 0.5 mg.mL-1) and lower activity for Escherichiacoli (MIC 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…A wide range of such extracts can be found in the literature, including extracts of white ginseng 34 , green tea 35 , peanut red skin 36 or roselle hibiscus 37 . In addition, antibacterial properties of alginate films can also be provided by tansy essential oil 38 , lemongrass essential oil 30 , basil leaf ethanol extract 39 or brown propolis extract 40 . Chestnut extracts used as antibacterial agents in different polysaccharide-based films have been indicated by recent studies 41 45 as well.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of such extracts can be found in the literature, including extracts of white ginseng 34 , green tea 35 , peanut red skin 36 or roselle hibiscus 37 . In addition, antibacterial properties of alginate films can also be provided by tansy essential oil 38 , lemongrass essential oil 30 , basil leaf ethanol extract 39 or brown propolis extract 40 . Chestnut extracts used as antibacterial agents in different polysaccharide-based films have been indicated by recent studies 41 45 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al. (2023) reported novel edible coatings cassava starch‐based bionanocomposites obtained from oat and wheat straw, and the coatings effectively shut off O 2 and maximize the desirable quality of strawberry. Chia seed mucilage–bacterial cellulose nano‐fiber was applied in strawberries, and it could inhibit PPO activity and maintain polyphenol content, which led to less o ‐quinone generation (Mousavi et al., 2021).…”
Section: Intervention Strategies For O‐quinone and O‐quinone‐induced ...mentioning
confidence: 99%
“…There are many edible materials that can be used for coating, usually biological materials, such as protein, polysaccharide, carboxymethyl cellulose, and commercial starch (Kim et al, 2022;Plesoianu & Nour, 2022). Costa et al (2023) reported novel edible coatings cassava starch-based bionanocomposites obtained from oat and wheat straw, and the coatings effectively shut off O 2 and maximize the desirable quality of strawberry. Chia seed mucilage-bacterial cellulose nano-fiber was applied in strawberries, and it could inhibit PPO activity and maintain polyphenol content, which led to less o-quinone generation (Mousavi et al, 2021).…”
Section: Food Packaging Techniques For Oxygen Isolationmentioning
confidence: 99%
“…After 5 minutes at 50°C, the color of the solution changed from greenish to blue, and the absorbance was recorded at 760 nm, equipment NOVA 2000UV. [33] In addition, a gallic acid (25,50,100,200,300,400, 500 e 600 µg/mL) (Sigma-Aldrich) standard curve was plotted (Absorbance = 0.12497+ 0.12951 concentration of gallic acid (R 2 = 0.999)).…”
Section: Propolis' Phenols Quantificationmentioning
confidence: 99%
“…[24] Brown propolis was incorporated in alginate membranes to be used as a food covering when the membrane was active against gram-positive bacteria. [25] Sodium carboxymethylcellulose (CMC) is one of the main polymers derived from cellulose. It is soluble in water, and its viscosity and adsorption capacity can be modulated by varying pH, concentration, and temperature.…”
Section: Introductionmentioning
confidence: 99%